A way forward for fundamental physics in space - A. Bassi; L. Cacciapuoti; S. Capozziello; S. Dell’Agnello; E. Diamanti; D. Giulini; L. Iess; P. Jetzer; S. K. Joshi; A. Landragin; C. Le Poncin-Lafitte; E. Rasel; et al. (npj Microgravity, 2022)
Abstract Space-based research can provide a major leap forward in the study of key open questions in the fundamental physics domain. They include the validity of Einstein’s Equivalence principle, the origin and the nature of dark matter and dark energy, decoherence and collapse models in quantum mechanics, and the physics of quantum many-body systems. Cold-atom sensors and quantum technologies have drastically changed the approach to precision measurements. Atomic clocks and atom interferometers as well as classical and quantum links can be used to measure tiny variations of the space-time metric, elusive accelerations, and faint forces to test our knowledge of the physical laws ruling the Universe. In space, such instruments can benefit from unique conditions that allow improving both their precision and the signal to be measured. In this paper, we discuss the scientific priorities of a space-based research program in fundamental physics.